Analisis Pengelolaan Limbah Medis Padat Di Rumah Sakit Cinere Depok Tahun 2022 Berdasarkan Kepmenkes Nomor 1204/MENKES/SK/X/2004 - Abdan Shofuh Adlu Syakur (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
A health facility is a meeting place for people who are affected by disease and who provide health services, as well as for people and their surroundings. Therefore, it can spread disease if the hospital environment conditions are inappropriate; one that is generated from the hospital is waste. The objective of this study is to be able to find out the analysis of the management of solid medical waste at the Puri Cinere Depok Hospital in 2022. The results of the research on solid medical wastes have been carried out in accordance with the operational standards contained in the Sanitation Hospital according to Kemenkes No. 1204/MENKES/SK/X/2004. The purpose of the clearance is to make disposal and destruction easier so that there are no mistakes in the final process. The collection of waste from the hospital to the B3 temporary storage facility is carried out so that the waste is properly sorted before being placed in the temporary shelter so that it can be disposed of and handled properly in the final process. The disposal used for the disposal of waste at the temporary disposal site is good because it has already carried out the sorting well and adjusted the operational standards for the containers used. The transportation carried out by Cinere Depok Puri Hospital has been in accordance with the procedures established by the government, as the transportation is carried out by Oxularry officers with self-protection equipment provided for safety in transportation, either from the room to the storage site or from the warehouse to the final disposal site. The collection to the final disposal site from the temporary storage site is sufficiently good, as it is sorted and weighed before being taken to the last disposal place. The final disposal or disposal of waste is already working together with PT. Prasadha Pamunah Limbah Industri (PPLi) because it does not have an inquirer and land for disposal, so the Hospital Puri Cinere Depok uses a third party that has been authorized and certified, but for wastewater management, it has been assured that it can be itself because it already has the equipment.